2005
DOI: 10.1074/jbc.m504942200
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Expression Imbalance of Human mu Opioid Receptor (OPRM1) Caused by Variant A118G

Abstract: As a primary target for opioid drugs and peptides, the mu opioid receptor (OPRM1) plays a key role in pain perception and addiction. Genetic variants of OPRM1 have been implicated in predisposition to drug addiction, in particular the single nucleotide polymorphism A118G, leading to an N40D substitution, with an allele frequency of 10 -32%, and uncertain functions. We have measured allele-specific mRNA expression of OPRM1 in human autopsy brain tissues, using A118G as a marker. In 8 heterozygous samples measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
435
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(472 citation statements)
references
References 43 publications
21
435
3
5
Order By: Relevance
“…Our model raises the possibility that NTX reduces impulsive choice in proportion to the degree of k-receptor mediated effect relative to m-receptor mediated effect. This notion is supported by data showing that people with the A118G m-receptor polymorphism show reduced m-receptor expression (Zhang et al, 2005), and more effective NTX-mediated abstinence from alcohol (Oslin et al, 2003). However, our small sample sizes make it difficult to conclusively attribute the impulsive choice differences we find between the AA and CS groups to propensity to alcoholism per se, or other related factors, such as depression.…”
Section: Relevance To Alcoholismsupporting
confidence: 58%
See 1 more Smart Citation
“…Our model raises the possibility that NTX reduces impulsive choice in proportion to the degree of k-receptor mediated effect relative to m-receptor mediated effect. This notion is supported by data showing that people with the A118G m-receptor polymorphism show reduced m-receptor expression (Zhang et al, 2005), and more effective NTX-mediated abstinence from alcohol (Oslin et al, 2003). However, our small sample sizes make it difficult to conclusively attribute the impulsive choice differences we find between the AA and CS groups to propensity to alcoholism per se, or other related factors, such as depression.…”
Section: Relevance To Alcoholismsupporting
confidence: 58%
“…Given that NTX acts at both m-and k-opioid receptors, which exert opposing effects on forebrain DA release (Spanagel et al, 1992;Herz and Spangel, 1995;Margolis et al, 2006), differential effects of NTX on DA levels could be due to differences in relative m-and k-mediated effects of NTX, as depicted in Figure 6. Relative m-receptor to k-receptor blockade effects would be expected to differ in subjects with low circulating levels of endogenous m-receptor ligands, as is the case with alcoholics and their offspring (Govoni et al, 1983;Vescovi et al, 1992;del Arbol et al, 1995;Dai et al, 2005), or in subjects with low levels of m-receptor expression, as is found in subjects with low frontal DA levels (Berthele et al, 2005) owing to their catechol-O-methyltransferase genotype (Meyer-Lindenberg et al, 2005), and in subjects with the A118G polymorphism of the m-receptor (Zhang et al, 2005). This latter polymorphism has also shown a functional differentiation in the therapeutic response to NTX (Oslin et al, 2003), and has distinguished alcoholics from non-alcoholics in some populations (Bart et al, 2005).…”
Section: Discussion Ntx Effects On Impulsive Choicementioning
confidence: 99%
“…These cells were chosen because, in the mu opioid receptor, amino-acid position 40 is a putative site of glycosylation. Further, a recent report on human receptors harvested from post-mortem brain tissue has found that some of the functional effects seen by Bond et al may be related to a decrease in mu opioid receptor mRNA expression in subjects with a variant 118G allele (Zhang et al, 2005). Other studies have also identified reduced receptor expression in transfected cell lines of receptors encoded by the 118G allele, a finding also noted in our ongoing studies (Beyer et al, 2004;Kroslak et al, 2003).…”
Section: Introductionsupporting
confidence: 62%
“…We have developed a robust procedure for allele-specific measurement of mRNA expression using a fluorescence-based primer extension assay to quantify real-time PCR amplification. 51,52 We have successfully applied this approach to identifying functional cis-acting polymorphisms in MDR1 53 and OPRM. 52 In the present study, we used this method to measure AEI for SERT mRNA in 48 postmortem pons tissues sections from individuals heterozygous for a marker SNP (rs1042173) in the 3 0 UTR of SERT mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…51,52 We have successfully applied this approach to identifying functional cis-acting polymorphisms in MDR1 53 and OPRM. 52 In the present study, we used this method to measure AEI for SERT mRNA in 48 postmortem pons tissues sections from individuals heterozygous for a marker SNP (rs1042173) in the 3 0 UTR of SERT mRNA. Although we have detected a limited degree of allelic variations in mRNA expression, this did not correlate with the SERTLPR promoter polymorphism.…”
Section: Introductionmentioning
confidence: 99%